PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN EKSPLOITASI SEKSUAL DI KOTA PEKANBARU - Sri Indrayani; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Children are the next generation of the nation and the next generation of development, that is, the generation prepared as subjects for implementing sustainable development and holding the future control of a country, Indonesia is no exception. The protection of Indonesian children means protecting the potential of human resources and building a just and prosperous human being, spiritual material based on the Pancasila and the 1945 Constitution of the Republic of Indonesia. Provision of protection for children as victims of sexual exploitation is to provide security from threats posed by perpetrators or other syndicates and get guidance on the mentality that has been corrupted by the perpetrators. For this reason, the role of the government is needed to prevent and eradicate the crime of sexual exploitation, so that no Indonesian children will be victims of the crime.This type of research can be classified as sociological, because in this study the authors directly conducted research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru City Police Department, while the population and sample were all parties related to the problem examined in this study, the data source used primary data, secondary data, and tertiary data, data collection techniques in this study with observation, interviews, and literature study.From the results of the study it can be concluded that the rights of children as victims have not been fully fulfilled, in the application of providing legal protection given to children as victims of sexual exploitation there are obstacles or obstacles.Keywords : Protection-Child-Criminal Acts of Sexual Exploitation